vault backup: 2025-02-18 09:51:11
This commit is contained in:
parent
0e758ef864
commit
0eeea19351
@ -122,6 +122,8 @@ $$ \dfrac{d}{dx}(\dfrac{f(x)}{g(x)}) = \dfrac{f'(x)g(x) -f(x)g'(x)}{(g(x))^2} $
|
|||||||
$$ \dfrac{d}{dx} e^x = e^x $$
|
$$ \dfrac{d}{dx} e^x = e^x $$
|
||||||
$$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$
|
$$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$
|
||||||
for all $a > 0$
|
for all $a > 0$
|
||||||
|
|
||||||
|
|
||||||
# Logarithms
|
# Logarithms
|
||||||
|
|
||||||
For natural logarithms:
|
For natural logarithms:
|
||||||
@ -129,17 +131,27 @@ $$ \dfrac{d}{dx} \ln |x| = \dfrac{1}{x} $$
|
|||||||
|
|
||||||
For other logarithms:
|
For other logarithms:
|
||||||
$$ \dfrac{d}{dx} \log_a x = \dfrac{1}{(\ln a) x}$$
|
$$ \dfrac{d}{dx} \log_a x = \dfrac{1}{(\ln a) x}$$
|
||||||
When solving problems that make use of logarithms, consider making use of logarithmic properties to make life easier, eg:
|
When solving problems that make use of logarithms, consider making use of logarithmic properties to make life easier:
|
||||||
$$ \ln(\dfrac{x}{y}) = \ln(x) - \ln(y) $$
|
$$ \ln(\dfrac{x}{y}) = \ln(x) - \ln(y) $$
|
||||||
|
$$ \ln(a^b) = b\ln(a) $$
|
||||||
|
## Logarithmic Differentiation
|
||||||
|
This is used when you want to take the derivative of a function raised to a function ($f(x)^{g(x)})$
|
||||||
|
|
||||||
|
1. $\dfrac{d}{dx} x^x$
|
||||||
|
2. $y = x^x$
|
||||||
|
3. $\ln y = \ln x^x$
|
||||||
|
4. $\ln(y) = x*\ln(x)$
|
||||||
|
5. $\dfrac{d}{dx} \ln y = \dfrac{d}{dx} x \ln x$
|
||||||
|
6. $\dfrac{1}{y} \dfrac{dy}{dx} = 1 * \ln x + x * \dfrac{1}{x}$
|
||||||
# Chain Rule
|
# Chain Rule
|
||||||
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
||||||
## Examples
|
## Examples
|
||||||
> Given the function $(x^2+3)^4$, find the derivative.
|
> Given the function $(x^2+3)^4$, find the derivative.
|
||||||
|
|
||||||
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$.
|
||||||
5. First find the derivative of the outside function function ($f(x) = x^4$):
|
7. First find the derivative of the outside function function ($f(x) = x^4$):
|
||||||
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
$$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$
|
||||||
6. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
8. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$.
|
||||||
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
$$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$
|
||||||
> Apply the chain rule to $x^4$
|
> Apply the chain rule to $x^4$
|
||||||
|
|
||||||
@ -175,7 +187,7 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$
|
|||||||
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
- Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$.
|
||||||
|
|
||||||
Given these facts:
|
Given these facts:
|
||||||
7. Let $y$ be some function of $x$
|
9. Let $y$ be some function of $x$
|
||||||
8. $\dfrac{d}{dx} x = 1$
|
10. $\dfrac{d}{dx} x = 1$
|
||||||
9. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
11. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\
|
||||||
|
|
||||||
|
Loading…
x
Reference in New Issue
Block a user